PENERAPAN TEST KONSOLIDASI METODA CONSTANT RATE OF STRAIN (CRSCONSOLIDATION TEST) PADA TANAH GAMBUT BERSERAT - Ferry Fatnanta (Universitas Pasir Pengaraian, 2014)
The studies on the determination of strain rate on the consolidation method of CRS test has been done on clayhave different plasticity. Beside that, the CRS method to study consolidation of clay with organic content of 45%organic content has also been done. Until now it has never done studies use CRS method for fibrous peat soil in whichthe fibrous peat soil organic matter content of more than 75%. Therefore, in applying the study attempted to test theconsolidation method of CRS on fibrous peat soil. Issues discussed in this study is how the rate of change of the voidratio compression behavior of fibrous peat soil on consolidation test method of constant strain rate.For this study, the undisturbed soil sample was taken from the Tropical Peat Research Center, at Pekantua village,Riau province. The void ratio exchange rate chosen for for the constant rate of strain consolidation test method was0,4; 0,2; 0,05; 0,02 and 0,01 per menit.